A metal-lustrous porphyrin foil. Issue 77 (15th September 2017) - Morisue, Mitsuhiko; Hoshino, Yuki; Shimizu, Masaki; Tomita, Shogo; Sasaki, Sono; Sakurai, Shinichi; Hikima, Takaaki; Kawamura, Ayaka; Kohri, Michinari; Matsui, Jun; Yamao, Takeshi
Abstract : A metal-lustrous self-standing film, named "porphyrin foil", formed from a glass-forming polymeric porphyrin. Abstract : A metal-lustrous self-standing film, named "porphyrin foil", was formed from a glass-forming polymeric porphyrin. The amorphous glass nature of the porphyrin foil played a key role in spontaneously producing a smooth surface. Its sharp contrast in intense absorption and specular reflection of light at each wavelength provided a brilliant metallic lustre.